The old man's prayer - Khan, Saniyasnain; Bansal, Sujata (Goodword Books New Delhi, 2010)
The Old Man's Prayer is a touching story that follows an elderly man's heartfelt journey as he reflects on his life, sharing his wisdom and the transformative power of prayer in finding peace, hope, and connection with the divine.